2021
DOI: 10.1055/a-1369-9426
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Erytrocyte Oxidative Stress Markers in Children with Frequent Breath-Holding Spells

Abstract: Background Breath-holding spells (BHS) are common non-paroxysmal events with unknown pathophysiology. BHS have been associated not only with iron deficiency anemia (IDA) but also with oxidant/antioxidant imbalance and erythrocyte injury induced by hypoxia. The present study was designed to investigate the contribution of IDA in BHS and the oxidant/antioxidant balance in children with or without IDA in BHS and compare them with healthy controls.Additionally, the study also aimed to examine the effect of the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The analysis of MDA levels in blood samples has been extensively employed to investigate the role of oxidative stress in airway diseases. Various studies have examined different methodologies for measuring MDA in this sample, including serum, erythrocyte and lymphocyte MDA levels (S-, E- and L-MDA) [ 44 , 45 , 46 , 47 , 48 ]. However, the accurate measurement of MDA in biological samples can pose challenges due to its instability and susceptibility to degradation.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of MDA levels in blood samples has been extensively employed to investigate the role of oxidative stress in airway diseases. Various studies have examined different methodologies for measuring MDA in this sample, including serum, erythrocyte and lymphocyte MDA levels (S-, E- and L-MDA) [ 44 , 45 , 46 , 47 , 48 ]. However, the accurate measurement of MDA in biological samples can pose challenges due to its instability and susceptibility to degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane changes and damage to erythrocytes due to ROSinduced oxidative stress, have been demonstrated (17). Several studies have reported that the concentrations and activities of antioxidant enzymes such as glutathione peroxidase (GSH-Px), catalase (CAT) and superoxide dismutase (SOD) decreased and oxidant stress increased in IDA (18,19). Aycicek et al (20), have found that total oxidant status (TOS) and oxidative stress index (OSI) were higher in patients with IDA, while total thiol (-SH) and total antioxidant capacity (TAC) levels were lower than in the control group.…”
Section: Discussionmentioning
confidence: 99%